Korelasi Kadar Hepsidin dan Reticulocyte Hemoglobin pada Penderita Gagal Ginjal Terminal dengan Hemodialisis Reguler - Ginting, Almaycano; Ganie, Ratna Akbari; Nasution, Syafrizal (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction Anemia is a frequent complication in Chronic Kidney Disease (CKD), especially in End-State Renal Disease (ESRD) undergoing hemodialysis (HD). Reticulocyte Hemoglobin (Ret.He) represents the average value of Hemoglobin (Hb) distribution in reticulocytes and the availability of iron in the process of erythropoiesis. Hepcidin is a hormone that plays a role in the regulation and metabolism of iron. Hepcidin correlation and Ret.He levels in ESRD patients undergoing regular HD is not known clearly. The aim of study is to determine the correlation of hepcidin and Ret.He in ESRD patients undergoing regular HD.Methods This is a cross sectional study that were conducted at H.Adam Malik Hospital, December 2015-March 2016. Subjects were ESRD outpatients undergoing regular HD in Hemodialysis Unit of H. Adam Malik Hospital over 3 months with a frequency of two times per week and signed the informed consent. Spearman correlation test was used for statistical analysisResults The median levels of hepcidin (0.3 ng/ml) and Ret.He (33.6 pg), were found in 31 subjects. There is a weak correlation but insignificant of hepcidin and Ret.He (r = 0.135, p = 0.467).Conclusion There was no correlation of hepcidin and Ret.He in ESRD patients undergoing regular HD.Keywords : Anemia, Hepcidin in End-Stage Renal Disease, Reticulocyte Hemoglobin, ,Regular hemodialysis, iron status